Exercise-induced anaphylaxis: A clinical view - Povesi Dascola Carlotta; Caffarelli Carlo (BMC, 2012)
Abstract Exercise-induced anaphylaxis (EIA) is a distinct form of physical allergy. The development of anaphylaxis during exertion often requires the concomitant exposure to triggering factors such as intake of foods (food dependent exercise-induced anaphylaxis) or drugs prior to exercise, extreme environmental conditions. EIA is a rare, but serious disorder, which is often undetected or inadequately treated. This article summarizes current evidences on pathophysiology, diagnosis and management. We reviewed recent advances in factors triggering the release of mediators from mast cells which seems to play a pathogenetic role. A correct diagnosis is essential to avoid unnecessary restricted diet, to allow physical activity in subjects with EIA dependent from triggering factors such as food, and to manage attacks. An algorithm for diagnosing EIA based on medical history, IgE tests and exercise challenge test has been provided. In the long-term management of EIA, there is a need for educating patients and care-givers to avoid exposure to precipitating factors and to recognize and treat episodes. Future researches on existing questions are discussed.